Effectiveness of the application of an educational program based on the Health Belief Model (HBM) in Adopting Preventive Behaviors from Self-Medication among Women in Iran. A rRandomized Controlled Trial - Movahed, Ehsan; Rezaee Moradali, Monireh; Saeed Jadgal, Mohammad; Zareipour, MoradAli; Tasouji Azari, Mina (Investigación y Educación en Enfermería, 2023)
Objective. To evaluate the effectiveness of the application of an educational program based on the Health Belief Model (HBM) in Adopting Preventive Behaviors from Self- Medication among Women in Iran. Methods. Interventional study with pre and post phases. 200 women referring to the health centers of Urmia were selected by simple random sampling, divided into two groups of treatment and control. Data collection instruments were researcher- devised questionnaire including the questionnaire of Knowledge of Self-medication, the Questionnaire of Preventive Behaviors from Self medication, and the questionnaire of Health Belief Model. The questionnaires were assessed for expert validity and then, were checked for reliability. The educational intervention was conducted for the treatment group during four weeks four 45-minute sessions. Results. The average scores of knowledge, perceived susceptibility, perceived severity, perceived benefits, perceived barriers, cues to action, self-efficiency, and post-intervention performance in have increased in treatment group, comparing to the control group, All findings were statistically significant (p<0.05). Furthermore, social media, doctors, and disbelief in self- medication were more effective in increasing awareness and encouraging to have proper medication, also, the highest self-medication was in taking pain-relievers, cold tablets and antibiotics, which showed significant decrease in treatment group after the intervention. Conclusion. The educational program based on Health Belief Model was effective in reducing the self-medication among the studied women. Furthermore, it is recommended to use social media and doctors to improve the awareness and motivation among people. Thus, applying the educational programs and plans according to the Health Belief Model can be influential in reducing the self-medication.